Body acceptance by others: Refinement of the construct, and development and psychometric evaluation of a revised measure – The Body Acceptance by Others Scale-2. (March 2021) - Swami, Viren; Todd, Jennifer; Stieger, Stefan; Furnham, Adrian; Horne, George; Tylka, Tracy L.
Highlights: Scores on the Body Acceptance by Others Scale-2 (BAOS-2) are unidimensional. BAOS-2 scores have adequate internal consistency and 4-week test-retest reliability. BAOS-2 scores have good convergent, construct, criterion, discriminant, and incremental validity. BAOS-2 scores are invariant across gender and nationality (United Kingdom and United States). Abstract: The Body Acceptance by Others Scale (BAOS) measures the degree to which individuals perceive body acceptance by others, but its factor structure is questionable. Here, we developed a revision of the BAOS (i.e., the BAOS-2) by designing novel items reflective of generalised perceptions of body acceptance by others. In three studies, we examined the psychometrics of the 13-item BAOS-2. Study 1, with United Kingdom adults ( N = 601), led to the extraction of a unidimensional model of BAOS-2 scores and provided evidence of 4-week test-retest reliability. Study 2, with United Kingdom adults ( N = 423), indicated that the unidimensional model of BAOS-2 scores had adequate fit and that scores were invariant across gender. Study 2 also provided evidence of convergent, construct, criterion, discriminant, and incremental validity. Study 3 cross-validated the fit of the unidimensional model in adults from the United State ( N = 503) and provided evidence of invariance across gender and national group. Internal consistency coefficients of BAOS-2 scores were adequate across all three studies. There were no significant gender differences in BAOS-2 scores and a significant national difference had a negligible effect size. Thus, the BAOS-2 is a psychometrically-sound measure that can be utilised in future research.